Compound containing heteroaromatic ring and keto moiety and application thereof
By using compounds containing heteroaromatic rings and ketone groups to prepare a change color polymer material, the problem of existing intraocular lenses showing color under any light conditions is solved, the patient's visual adaptability and vision improvement is achieved, and the natural light transmission performance of the human eye is simulated.
Patent Information
- Application Number
- CN202510356110.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-24
- Publication Date
- 2025-08-12
AI Technical Summary
The existing yellow and photochromic intraocular lenses appear color under any light conditions, resulting in poor visual adaptability in patients with poor vision and sudden changes in vision when the light changes, which cannot alleviate the discomfort of cataract patients.
A compound containing heteroaromatic ring and ketone structure is used to prepare a color-changing polymer material, which is used to make an intraocular lens, making it light yellow in an aqueous environment, and becomes colorless after receiving light, simulating the light-transmitting properties of the natural lens of the human eye.
The patient's adaptability to light has been improved, and the visual ability after surgery has been improved, including the improvement of color vision recognition, dark vision and contrast sensitivity, while maintaining the ability to block ultraviolet rays and some blue-violet light.
Smart Images

Figure BDA0005327750650000021 
Figure BDA0005327750650000041 
Figure BDA0005327750650000061
Abstract
Description
Technical Field
[0001] The present invention relates to the field of ophthalmic medical materials, in particular to a compound containing a heteroaromatic ring and a ketone group and application thereof. Background Art
[0002] Cataract surgery to replace the intraocular lens is currently the most effective treatment for cataracts. Visually, intraocular lenses are divided into yellow and colorless intraocular lenses. The two types of intraocular lenses are made of different materials, resulting in different transmittances to ultraviolet and visible light. It is generally believed that the wavelength range of ultraviolet light that the human eye is exposed to is 200nm-380nm, and the wavelength range of visible light is 380nm-780nm, of which violet light (380nm-440nm) and blue light (440nm-500nm) constitute the short-wavelength portion of visible light. The various structures in the human eye have different transmittances to light of different wavelengths. Light with a wavelength less than 300nm is basically absorbed by the cornea, while ultraviolet light with a wavelength between 300nm-380nm is absorbed by the iris or lens. Currently, both types of intraocular lens materials on the market have the ability to absorb ultraviolet rays. The yellow intraocular lens material contains chromophore compounds, which have the ability to partially absorb blue-violet light with a wavelength between 380nm and 500nm. It is also called blue-light filtering IOL (BLF IOL); because of its yellow appearance, it is also called "yellow-lens" IOL.
[0003] The chromophore compound added to the yellow intraocular lens material is usually a permanent yellow compound, or a photochromic compound. Intraocular lens materials incorporating permanent yellow compounds simulate the varying degrees of yellowing that occurs in the natural lens with age. This provides a certain degree of adaptability for patients who are replacing their intraocular lenses, but due to its permanent yellow color, patients always see things in a colored state, and thus such lenses cannot provide patients with sufficient vision improvement. Intraocular lenses incorporating photochromic compounds appear colored when exposed to light and appear colorless when not exposed to light. Such lenses can reduce the intensity of light entering the eye in strong light, thereby avoiding discomfort under strong light, but this type of lens cannot alleviate the discomfort caused by the sudden "brightening" of cataract patients in the early stages of IOL replacement.
[0004] Therefore, there is a need for a color-changing compound that can solve the above problems after being incorporated into an intraocular lens. Summary of the Invention
[0005] To solve the above problems, the present invention provides a compound containing a heteroaromatic ring and a ketone structure in its molecular structure, a color-changing polymer containing the compound, and the use of the above compound and polymer in the preparation of artificial crystal materials.
[0006] In a first aspect, the present invention provides a compound having formula (I-1) or (I-2):
[0007]
[0008] in,
[0009] R1 is H, C 1-5 Alkyl; R2 is C 1-20 Alkylene; R3 is selected from H, -NH2, -OH, C 1-20 Alkyl, C 1-20 Alkoxy, -NHC 1-20 Oxygen, and -N(C 1-20 alkyl)2; and R c Does not exist or is C 1-5 alkyl;
[0010] L is selected from -O-, -NH-, -CO-, -SO-, -SO2-, -N(C 1-20 alkyl)-, -CONH-, and -CON(C 1-20 alkyl)-;
[0011] X is selected from O, S, CH2 and NH; and
[0012] Q1, Q2 and Q3 are each independently selected from N, CH, and CR4, wherein R4 is selected from halogen (e.g., F, Cl, Br, I), -OH, -NH2, -NO2, -CN, C 1-20 Alkyl, C 1-20 Alkoxy, -NHC 1-20 Alkyl, -N(C 1-20 Alkyl)2, -COOH, -COC 1-20 Alkyl, -COOC 1-20 Alkyl, -OC 1-20 Alkyl, -CONHC 1-20 Alkyl, -CON(C 1-20 alkyl)2, 6-20 membered aryl, and 5-20 membered heteroaryl.
[0013] The compound is light yellow and can become colorless in an aqueous environment.
[0014] In a second aspect, the present invention provides a color-changeable polymer material, comprising the compound of the first aspect.
[0015] In a third aspect, the present invention provides an intraocular lens comprising the compound of the first aspect or the polymer of the second aspect, which can simulate the light transmission properties of the natural lens of the human eye.
[0016] The compounds and / or polymer materials provided by this invention can effectively block ultraviolet light and absorb some blue-violet light. Due to their color-changing properties, when used to manufacture intraocular lenses, the resulting intraocular lenses can mimic the light transmission properties of the natural human lens, helping patients undergoing intraocular lens surgery adapt to the light and achieving better postoperative vision. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The diagram shows a process in which the compound of formula (I-1) of the present invention absorbs light energy, converts to an excited state, and finally forms a colorless compound in an aqueous environment.
[0018] Figure 2 The process of compound 4 absorbing light energy, converting to an excited state, and finally forming a colorless compound in an aqueous environment is shown.
[0019] Figure 3 The diagram shows the process of compound 5 absorbing light energy, converting to an excited state, and finally forming a colorless compound in an aqueous environment.
[0020] Figure 4 The light transmission curves of the IOL before implantation and 1 month after simulated implantation are shown.
[0021] Figure 5 Shown are the color changes of the IOL before implantation and 1 month after simulated implantation. DETAILED DESCRIPTION
[0022] A more detailed description of the present invention is provided below. However, it should be understood that the following embodiments and accompanying drawings are intended to illustrate the present invention only and do not constitute any limitation. The actual scope of protection of the present invention is set forth in the claims. It should be understood that any modifications and variations may be made without departing from the spirit of the present invention.
[0023] To make the objectives, technical solutions, and advantages of the present invention more clearly understood, the present invention will be further described in detail below with reference to the following examples. The specific embodiments described herein are intended only to illustrate the present invention and are not intended to limit the present invention in any way. In addition, in the following description, descriptions of known structures and technologies are omitted to avoid unnecessary confusion about the concepts of the present disclosure. Such structures and technologies are also described in many publications.
[0024] definition
[0025] The term "alkyl" as used herein refers to a monovalent group in the form of a straight chain, branched chain or ring. 1-20Alkyl groups include those having 1 to 20 carbon atoms, for example, those having 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20 carbon atoms. 1-15 Alkyl, C 1-10 Alkyl and C 1-5 Alkyl groups include those having 1-15, 1-10, and 1-5 carbon atoms, respectively. For example, C 1-5 Alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, cyclopropyl, cyclobutyl, cyclopentyl and the like.
[0026] The term "alkylene" as used herein refers to a divalent group formed by removing a hydrogen atom from an alkyl group. Except for methylene, preferably, the removed hydrogen atoms are not on the same carbon. Examples of alkylene groups include, but are not limited to, methylene, ethylene, propylene, and the like.
[0027] The term "alkoxy" as used herein refers to an -O-alkyl group, such as -OC 1-10 Alkyl, preferably -OC 1-5 Alkyl, more preferably -OC 1-3 Non-limiting examples of alkoxy groups include methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, sec-butoxy, isobutoxy, tert-butoxy, n-pentoxy, n-hexoxy, cyclopropyloxy, cyclobutyloxy, and the like.
[0028] The term "aryl" refers to a ring system (preferably a 6-10 membered aromatic ring) having a total of 6 to 20 ring members (or ring atoms). In certain embodiments of the present invention, "aryl" refers to an aromatic ring system, which includes but is not limited to phenyl.
[0029] The term "heteroaryl" refers to a heterocyclic group having aromaticity, including monocyclic and polycyclic aromatic groups. Non-limiting examples of heteroaryl include thienyl, furyl, pyrrolyl, pyrazolyl, imidazolyl, oxazolyl, isoxazolyl, triazolyl, thiazolyl, pyridyl, pyrazinyl, pyridazinyl, pyrimidinyl, benzimidazolyl, benzothiazolyl, benzoxazolyl, benzindazolyl, quinazolinyl, and indolyl.
[0030] The term "halogen" refers to F, Cl, Br, I, or isotopes thereof.
[0031] An intraocular lens, also known as an artificial lens (IOL), is an optical lens made of artificial synthetic materials. It is primarily used to replace the cloudy lens of the human eye to improve vision. Cataract surgery is the most common application of IOL implants. IOLs are also used to correct some refractive errors, such as high myopia. In this article, the terms "intraocular lens" and "artificial lens" are used interchangeably.
[0032] The first aspect of the present invention provides a compound having formula (I-1) or (I-2):
[0033]
[0034] in,
[0035] R1 is H, C 1-5 Alkyl; R2 is C 1-20 Alkylene; and R3 is selected from H, -NH2, -OH, C 1-20 Alkyl, C 1-20 Alkoxy, -NHC 1-20 Oxygen, and -N(C 1-20 alkyl)2; and R c Does not exist or is C 1-5 alkyl;
[0036] L is selected from -O-, -NH-, -CO-, -SO-, -SO2-, -N(C 1-20 alkyl)-, -CONH-, and -CON(C 1-20 alkyl)-;
[0037] X is selected from O, S, CH2 and NH; and
[0038] Q1, Q2 and Q3 are each independently selected from N, CH, and CR4, wherein R4 is selected from halogen (e.g., F, Cl, Br, I), -OH, -NH2, -NO2, -CN, C 1-20 Alkyl, C 1-20 Alkoxy, -NHC 1-20 Alkyl, -N(C 1-20 Alkyl)2, -COOH, -COC 1-20 Alkyl, -COOC 1-20 Alkyl, -OC 1-20 Alkyl, -CONHC 1-20 Alkyl, -CON(C 1-20 alkyl)2, 6-20 membered aryl, and 5-20 membered heteroaryl.
[0039] In some embodiments, R1 is H, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl or tert-butyl; preferably, R1 is H or methyl.
[0040] In some embodiments, R2 is C 1-15 In some embodiments, R2 is C 1-10 In some embodiments, R2 is C 1-5 In some embodiments, R2 is C 1-3 In some embodiments, R2 is methylene or ethylene.
[0041] In some embodiments, R3 is selected from H, -NH2, -OH, C 1-15 Alkyl, C 1-15 Alkoxy, -NHC 1-15 Alkyl, and -N(C 1-15 In some embodiments, R3 is selected from H, -NH2, -OH, C 1-10 Alkyl, C 1-10 Alkoxy, -NHC 1-10 Alkyl, and -N(C 1-15 In some embodiments, R3 is selected from H, -NH2, -OH, C 1-5 Alkyl, C 1-5 Alkoxy, -NHC 1-5 Alkyl, and -N(C 1-5 In some embodiments, R3 is selected from H, -NH2, -OH, C 1-3 Alkyl, C 1-3 Alkoxy, -NHC 1-3 Alkyl, and -N(C 1-3 In some embodiments, R3 is methyl or ethyl. In some embodiments, R3 is methyl.
[0042] In some embodiments, R c is absent or selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, and tert-butyl. c Absent or methyl.
[0043] In some embodiments, L is selected from -O-, -NH-, -CO-, -SO-, -SO2-, -N(C 1-15 alkyl)-, -CONH-, and -CON(C 1-15 In some embodiments, L is selected from -O-, -NH-, -CO-, -SO-, -SO2-, -N(C 1-10 alkyl)-, -CONH-, and -CON(C 1-10 In some embodiments, L is selected from -O-, -NH-, -CO-, -SO-, -SO2-, -N(C 1-5 alkyl)-, -CONH-, and -CON(C 1-5 In some embodiments, L is selected from -O-, -NH-, -CO-, -SO-, -SO2-, -N(C 1-3 alkyl)-, -CONH-, and -CON(C 1-3 In some embodiments, L is -O- or -NH-.
[0044] In some embodiments, X is NH or CH2, preferably, X is NH.
[0045] In some embodiments, R4 is selected from halogen, -OH, -NH2, -NO2, -CN, C 1-15 Alkyl, C 1-15 Alkoxy, -NHC 1-15 Alkyl, -N(C 1-15 Alkyl)2, -COOH, -COC 1-15 Alkyl, -COOC 1-15 Alkyl, -OC 1-15 Alkyl, -CONHC 1-15 Alkyl, -CON(C 1-15 In some embodiments, R4 is selected from halogen, -OH, -NH2, -NO2, -CN, C 1-10 Alkyl, C 1-10 Alkoxy, -NHC 1-10 Alkyl, -N(C 1-10 Alkyl)2, -COOH, -COC 1-10 Alkyl, -COOC 1-10 Alkyl, -OC 1-10 Alkyl, -CONHC 1-10 Alkyl, -CON(C 1-10 In some embodiments, R4 is selected from halogen, -OH, -NH2, -NO2, -CN, C 1-5 Alkyl, C 1-5 Alkoxy, -NHC 1-5 Alkyl, -N(C 1-5 Alkyl)2, -COOH, -COC 1-5 Alkyl, -COOC 1-5 Alkyl, -OC 1-5 Alkyl, -CONHC 1-5 Alkyl, -CON(C 1-5 In some embodiments, R4 is selected from halogen, -OH, -NH2, -NO2, -CN, C 1-3 Alkyl, C 1-3 Alkoxy, -NHC 1-3 Alkyl, -N(C 1-3 Alkyl)2, -COOH, -COC 1-3 Alkyl, -COOC 1-3 Alkyl, -OC 1-3 Alkyl, -CONHC 1-3 Alkyl, -CON(C 1-3In some preferred embodiments, R4 is selected from halogen, -NH2, and -OH. In some embodiments, halogen is F, Cl, Br, or I; preferably, halogen is F, Cl, or Br; more preferably, halogen is F or Cl. In some embodiments, R4 is -NH2, -OH, or -F.
[0046] In some embodiments, one of Q1, Q2 and Q3 is CR4 and the others are CH. In some embodiments, Q1, Q2 and Q3 are CH at the same time. In some embodiments, in formula (I-1) A section has any of the following structures: In some embodiments, in formula (I-1) A section has any of the following structures: In some embodiments, in formula (I-2) A section has any of the following structures: In some embodiments, in formula (I-2) A section has any of the following structures: In some embodiments, in formula (I-2) The part has the following structure
[0047] In some embodiments, the compound of formula (I-1) is a compound having the following structure:
[0048]
[0049] In some embodiments, the compound of formula (I-2) is a compound having the following structure:
[0050]
[0051] The compound of the present invention is a light yellow compound, which can be converted into a colorless compound after being exposed to light in an aqueous environment.
[0052] Figure 1 The diagram shows a process in which the compound of formula (I-1) of the present invention absorbs light energy, converts to an excited state, and finally forms a colorless compound in an aqueous environment.
[0053] Figure 2 and 3 The process of compounds 4 and 5 absorbing light energy, converting to excited states, and finally forming colorless compounds in an aqueous environment is shown respectively.
[0054] A second aspect of the present invention provides a color-changeable polymer material, wherein the color-changeable polymer material comprises the compound according to the first aspect.
[0055] In some embodiments, the color-changing polymeric material is prepared by incorporating the compound of the first aspect into a polymeric matrix. In some embodiments, the amount of the compound incorporated into the color-changing polymeric material is 0.01 wt% to 10 wt%, preferably 0.05 wt% to 5 wt%, and more preferably 0.1 wt% to 1 wt% of the color-changing polymeric material.
[0056] In some embodiments, the color-changeable polymer material of the present invention is a high-water content material, with a water content of about 15% to 65%; about 18% to 50%; or about 22% to 45%.
[0057] In some embodiments, the color-changeable polymer material of the present invention is a low-water content material, with a water content of about 1% to 5%; about 1.5% to 3%; or about 2% to 3%.
[0058] As used herein, "moisture content" refers to the ratio of water contained in a material to its total mass or total volume, usually expressed as a percentage (such as mass moisture content or volume moisture content).
[0059] The moisture content of the color-changing polymer material of the present invention can affect the material's color change time. For color-changing polymer materials with high moisture content, the time required for the material to change from light yellow to colorless is at least 2 months, or at least 1 month. For color-changing polymer materials with low moisture content, the time required for the material to change from light yellow to colorless is at least 6 months, or at least 3 months.
[0060] In some embodiments, the color-changeable polymer material of the present invention can be prepared by first polymerizing a polymerizable monomer to form a polymer matrix, then formulating the compound into a solution, and soaking the polymer matrix, and at high temperature, causing the compound to swell and penetrate into the polymer matrix, thereby incorporating the compound described in the first aspect.
[0061] In some embodiments, the color-changeable polymer material of the present invention can be prepared by adding the compound of the present invention to a polymerization monomer mixture forming a polymer matrix, followed by bulk polymerization.
[0062] The polymerization method used is a polymerization method commonly used by those skilled in the art, such as but not limited to free radical polymerization, ionic random polymerization (cationic or anionic), block copolymerization and the like.
[0063] In some embodiments, the polymerized monomers forming the polymeric material of the present invention include a hydrophilic monomer, other shaping monomers, a crosslinking agent, and an initiator.
[0064] The hydrophilic monomers and other molding monomers used in the present invention are not particularly limited, provided that they contain a polymerizable double bond in their structure. Examples of polymerizable double bonds include, but are not limited to, vinyl, allyl, acryloyloxy, methacryloyloxy, acrylamide, methacrylamide, and vinyl ether groups. Examples of hydrophilic groups include, but are not limited to, hydroxyl, carboxyl, amino, primary, secondary, tertiary amine, amide, anhydride, aldehyde, epoxy, polyether, and polyester groups.
[0065] The hydrophilic monomer used in the present invention can be selected from hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, glyceryl acrylate, glyceryl methacrylate, vinyl pyrrolidone, dimethylacrylamide, acrylic acid, methacrylic acid, acrylamide, methacrylamide, N-hydroxymethyl acrylamide, N-hydroxymethyl methacrylamide, glycidyl acrylate, glycidyl methacrylate, 2-methacryloyloxyethyl phosphorylcholine, polyethylene glycol monoacrylate, polyethylene glycol methacrylate, methoxypolyethylene glycol monoacrylate, methoxypolyethylene glycol monomethacrylate, ethoxypolyethylene glycol monoacrylate, ethoxypolyethylene glycol monomethacrylate, polypropylene glycol monoacrylate, polypropylene glycol methacrylate, polyglycerol monoacrylate, polyglycerol monomethacrylate, and a mixture of two or more of the above monomers.
[0066] The main function of the hydrophilic monomer is to adjust the water content of the polymer material. Increasing the amount or proportion of the hydrophilic monomer in the polymer material can increase the water content of the polymer material; conversely, reducing the amount or proportion of the hydrophilic monomer can reduce the water content of the polymer material.
[0067] According to different moisture content requirements of the polymer material, the proportion of the hydrophilic monomer in the polymer material can be 5% to 50%, 10% to 40%, or 20% to 30%.
[0068] Other forming monomers used in the present invention can be selected from methyl methacrylate, methyl acrylate, ethyl methacrylate, ethyl acrylate, propyl methacrylate, propyl acrylate, isopropyl methacrylate, isopropyl acrylate, butyl methacrylate, butyl acrylate, isobutyl methacrylate, isobutyl acrylate, hexyl methacrylate, hexyl acrylate, methoxyethyl methacrylate, methoxyethyl acrylate, ethoxyethyl methacrylate, ethoxyethyl acrylate, ethoxyethoxyethyl methacrylate, ethoxyethoxyethyl acrylate, isooctyl methacrylate, isooctyl acrylate, isodecyl acrylate, isodecyl methacrylate, lauryl methacrylate, lauryl acrylate, myristyl methacrylate, propyl ... ethyl acrylate, 2-perfluorodecylethyl methacrylate, 2-perfluorodecylethyl acrylate, 2-(perfluorooctyl)ethyl methacrylate, 2-(perfluorooctyl)ethyl acrylate, phenoxyethyl acrylate, phenoxyethyl methacrylate, phenoxypolyethylene glycol acrylate, phenoxypolyethylene glycol methacrylate, phenylethyl acrylate, phenylethyl methacrylate, and mixtures of two or more of the foregoing monomers.
[0069] The main function of other molding monomers is to adjust the glass transition temperature and / or refractive index of the polymer material. Generally speaking, for polymer materials with high moisture content, a higher glass transition temperature can be designed, preferably above room temperature, above 20°C, above 25°C, above 30°C, or above 40°C; while for materials with low moisture content, a lower glass transition temperature can be designed, preferably below room temperature, preferably in the range of -40°C to 20°C, preferably in the range of -20°C to 20°C, preferably in the range of -10°C to 20°C, preferably in the range of 0°C to 20°C, preferably in the range of 0°C to 15°C, preferably in the range of 5°C to 15°C. The refractive index of the polymer material is preferably greater than 1.42, preferably greater than 1.46, preferably greater than 1.48, preferably greater than 1.50, preferably greater than 1.52, and preferably greater than 1.54.
[0070] In another embodiment, the color-changeable polymer material is composed of a polymer material selected from a polysiloxane structure as the main material, and its glass transition temperature can be selected from a lower glass transition temperature, selected from below -40°C, selected from below -60°C, and selected from below -80°C.
[0071] The proportion of other molding monomers in the material can be about 30% to 95%; about 50% to 85%; about 60% to 70%.
[0072] There are no particular limitations on the crosslinking agent used in the present invention, as long as it contains two or more polymerizable double bonds in its structure. Examples of polymerizable double bonds include, but are not limited to, vinyl, allyl, acryloyloxy, methacryloyloxy, acrylamide, methacrylamide, and vinyl ether.
[0073] The crosslinking agent can be selected from ethylene glycol diacrylate, ethylene glycol dimethacrylate, butylene glycol diacrylate, butylene glycol dimethacrylate, hexanediol diacrylate, hexanediol dimethacrylate, diethylene glycol diacrylate, diethylene glycol dimethacrylate, triethylene glycol diacrylate, triethylene glycol dimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, triethylolpropane triacrylate, triethylolpropane trimethacrylate, pentanediol diacrylate, pentanediol dimethacrylate, divinylbenzene, or a mixture of two or more of the foregoing.
[0074] The crosslinker itself can be a hydrophilic monomer. Its primary function in polymer materials is to enable the polymer molecules within the material to form a "network" structure that maintains its integrity in both aqueous and organic solvents, preventing dissolution or the release of free molecules in the solvent. This ensures the long-term stability and safety of the polymer material in the environment.
[0075] The proportion of the cross-linking agent in the polymer material is 0.1% to 10%, 0.5% to 5%, or 1% to 5%.
[0076] The initiator used in the present invention is not particularly limited as long as it can cause the polymerization of the above-mentioned monomers. According to different polymerization methods, different types of initiators can be used. Examples of initiators may include, but are not limited to, free radical initiators, such as azo initiators, and / or peroxide initiators; photoinitiators, such as azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptonitrile, benzoyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tert-butylperoxycarbonate-2-ethylhexyl ester, peroxy tert-amyl-2-ethylhexanoate, peroxy (2-ethylhexyl) carbonate tert-amyl, peroxy dilauroyl, bis(4-tert-butylcyclohexyl) peroxydicarbonate, peroxy di(hexadecyl) dicarbonate, peroxy dicarbonate bis(tetradecyl) dicarbonate Alkyl esters, dicumyl peroxide, 2,5-dimethyl-2,5-bis(2-ethylhexanoic acid peroxy)hexane, 2,5-dimethyl-2,5-di-tert-butylperoxy-3-hexyne, tert-butyl peroxy(2-ethylhexanoate), 1,1-di-tert-butylperoxycyclohexane, tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, tert-butyl 2-ethylbutane peroxycarboxylate, 1,1-di-tert-butylperoxy-3,3,5-trimethylcyclohexane, 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxynonane, bis(3,5,5-trimethylhexanoyl)propane ) peroxide, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, tert-butylperoxy-3,5,5-trimethylhexanoate, tert-butyl hydroperoxide, di-tert-butyl peroxide, tert-butyl peroxybenzoate, tert-butyl peroxyisopropyl formate, di(2-ethylhexyl) dicarbonate, tert-butyl peroxyacetate, hydroxyisopropylbenzene peroxide, diisopropylbenzene hydroperoxide, tert-butylisopropyl peroxide, tert-amyl hydroperoxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-N-propylphenylphosphine oxide, bis-(2 ,6-dichlorobenzoyl)-4-N-butylphenylphosphine oxide, diethoxyacetophenone, 1-hydroxycyclohexylphenyl ketone, 2-hydroxy-2-methylphenylacetone, riboflavin, and mixtures of two or more thereof; cationic initiators, such as protonic acids or Lewis acids, such as sulfuric acid, phosphoric acid, hydrochloric acid, trifluoroacetic acid, trichloroacetic acid, perchloric acid, aluminum trichloride, boron trifluoride, tin tetrachloride, zinc dichloride, titanium tetrabromide, titanium tetrachloride, etc.; and anionic initiators, such as alkali metals, organometallic compounds, tertiary amines, amino compounds of metals such as lithium, sodium, potassium, metal alkyl compounds, and butyllithium.
[0077] The proportion of the initiator in the polymer material may be about 0.05% to 5%; about 0.1% to 2%; about 0.1% to 1%.
[0078] In some embodiments, the color-changeable polymer of the present invention is formed by polymerizing a hydrophilic monomer, other forming monomers, a crosslinking agent, and a compound of the present invention in the presence of an initiator. In this method, the hydrophilic monomer, other forming monomers, the crosslinking agent, the compound of the present invention, and the initiator are first uniformly mixed, and then external energy is applied to the monomer mixture to initiate polymerization of the monomers, thereby forming a polymer material. The applied external energy can be selected from heating, ultraviolet radiation, visible light radiation, microwave radiation, radioactive ray irradiation, or a combination thereof.
[0079] The third aspect of the present invention provides an artificial lens, which is made of the color-changing polymer material of the second aspect, or contains the color-changing polymer material of the second aspect, and the artificial lens can simulate the light transmission performance of the natural lens of the human eye.
[0080] The artificial lens of the present invention is light yellow before implantation and in the early stage of implantation into the eye, and can absorb some blue-violet light. It will then gradually turn colorless over a period of time, thereby improving the visual ability of the recipient (for example, a patient who has had an artificial lens implanted through cataract surgery), including color vision, dark vision, contrast sensitivity, circadian physiological rhythm, etc.
[0081] In some embodiments, the intraocular lens of the present invention is light yellow before implantation or in the early stage of implantation (e.g., within at least 1 month of implantation), and has a spectral transmittance of no more than 10%; no more than 2%; or no more than 1% for ultraviolet light in the wavelength range of 370 nm or less. In some embodiments, the intraocular lens of the present invention has a spectral transmittance of no more than 10%; no more than 2%; or no more than 1% for ultraviolet light in the wavelength range of 380 nm or less before implantation or in the early stage of implantation. In some embodiments, the intraocular lens of the present invention has a spectral transmittance of no more than 10%; no more than 2%; or no more than 1% for ultraviolet light in the wavelength range of 400 nm or less before implantation or in the early stage of implantation. In some embodiments, the intraocular lens of the present invention has a transmittance of no more than 70%; no more than 75%; no more than 80%; no more than 85%; or no more than 90% for blue-violet light in the wavelength range of 400-500 nm or in the early stage of implantation. In some embodiments, the intraocular lens of the present invention has a transmittance of not less than 90%; not less than 92%; or not less than 95%; or not less than 98% for visible light in the wavelength range of 500-780nm and infrared light in the wavelength range above 780nm before implantation or in the early stage of implantation.
[0082] The intraocular lens of the present invention gradually becomes colorless and transparent after being implanted in the eye (for example, at least one month after being implanted in the eye), but can still maintain its ultraviolet blocking ability, for example, the spectral transmittance for ultraviolet rays in the wavelength range of 380nm or less is not higher than 10%; not higher than 2%; or not higher than 1%, but the transmittance for blue-violet light in the wavelength range of 400-500nm is not lower than 90%; not lower than 92%; even not lower than 95%; more even not lower than 98%; and / or the transmittance for visible light in the wavelength range of 500-780nm and infrared light in the wavelength range above 780nm is not lower than 90%; not lower than 92%; even not lower than 95%; more even not lower than 98%.
[0083] The intraocular lens of the present invention can be manufactured by bulk polymerization, which includes polymerizing the color-changing polymer material of the present invention in a circular mold, forming the raw material, and then processing the resulting polymer material by turning, milling, etc. to form the optical portion and support portion of the intraocular lens. The intraocular lens of the present invention can also be manufactured by first forming the polymer material of the present invention into the optical portion of the intraocular lens using a mold, and then forming the support portion by milling. The optical portion and support portion of the intraocular lens of the present invention can also be directly formed by mold molding, and then combined to obtain the finished intraocular lens of the present invention.
[0084] The intraocular lens of the present invention can have a high water content, ranging from about 15% to 65%; about 18% to 50%; or about 22% to 45%. After implantation, the intraocular lens gradually changes from a light yellow color to colorless, and its transmittance to blue-violet light in the wavelength range of 400-500 nm gradually increases to above 90%, and this stage takes at least two months; at least one month.
[0085] The intraocular lens of the present invention may have a low water content, ranging from about 1% to 5%; about 1.5% to 3%; about 2% to 3%. However, after implantation into the eye, it requires sufficient water to change its color from light yellow to colorless, and its transmittance to blue-violet light with a wavelength range of 400-500nm gradually increases to above 90%. The time required for this stage is at least 6 months; at least 3 months.
[0086] Example
[0087] The present invention will be described in more detail below through specific examples, but the scope of the present invention is not limited thereto.
[0088] The raw materials used in the examples were purchased from, for example, Jinan MaruDe Pharmaceutical Technology Co., Ltd., Shandong West Asia Chemical Co., Ltd. and Sigma-Aldrich (Shanghai).
[0089] Example 1: Preparation of compounds
[0090] 1. Preparation of Compound 4
[0091]
[0092] In a 1L round-bottom flask, 112.3g of 2-(4-(2-hydroxyethyl)phenyl)-5-amino-6-acetylbenzimidazole (0.38mol) and 50mL of triethylamine (TEA) were dissolved in 300mL of dichloromethane (CH2Cl2), and the flask was placed in an ice-water bath. 39.7g of methacryloyl chloride (0.38mol) was dissolved in 100mL of dichloromethane (CH2Cl2), then slowly added dropwise to the round-bottom flask to start the reaction and stir. The addition time was controlled to 4 hours, and then continued to stir at room temperature for 8 hours. After the reaction was completed, 500mL of ether was added to precipitate the product, and the precipitate was dissolved in CH2Cl2 again and precipitated with ether again. The crude product obtained by repeated precipitation was redissolved in CH2Cl2 and separated by silica gel chromatography using a 2:1 by volume hexane / ethyl acetate solution as the developing solvent. The separation endpoint was determined by silica gel thin-layer chromatography (TLC). The solution containing the target compound was concentrated by rotary evaporation to remove most of the solvent. The solution was then placed in a vacuum drying oven to remove all solvent, ultimately yielding pure compound 4 as a yellow solid (HPLC purity greater than 99%, yield 60%-65%).
[0093] 1 H NMR (400MHz): δ1.86(2H,s),2.25(2H,s),3.06(1H,t,J=4.75Hz), 4.39(1H,t,J=4.75Hz), 5.56(1H,d,J=3.8 6Hz), 6.05 (1H, d, J = 3.86Hz), 6.96 (1H, d, J = 0.50Hz), 7.55 (2H, ddd, J = 8.15, 1.38, 0.45Hz), 7.84 (ddd, J = 8.1 5,1.62,0.45Hz),8.16(1H,d,J=0.50Hz),1.86(2H,s),2.25(2H,s),3.06(1H,t,J=4.75Hz),4.39(1H,t,J=4 .75Hz),5.56(1H,d,J=3.86Hz),6.05(1H,d,J=3.86Hz),6.96(1H,s),7.56(2H,m),8.07(1H,m),8.15(1H,s).
[0094] 2. Preparation of other compounds
[0095] Compounds 1, 2, 3, and 5 were prepared using the same method as for Compound 4, except that Reactant A, shown in Table 1, was substituted for 2-(4-(2-hydroxyethyl)phenyl)-5-amino-6-acetylbenzimidazole, and Reactant B was substituted for methacryloyl chloride. All other conditions remained unchanged. The data for the resulting Compounds 1, 2, 3, and 5 are shown in Table 2.
[0096] Table 1:
[0097]
[0098] Table 2
[0099]
[0100]
[0101] Example 2: Preparation of high water content intraocular lens material
[0102] As shown in Table 3, the following components were mixed separately until each component was completely dissolved and stirred evenly. The resulting mixture was transferred to a cylindrical sealed mold for curing and molding. Curing was performed at 50°C for 6 hours and then at 100°C for 12 hours. After curing, polymer materials 1-8 were obtained.
[0103] The obtained polymer material was removed from the mold and further processed into a round button-shaped material sheet with a diameter of 14 mm and a thickness of 3 mm. The material sheet was washed with 80% ethanol solution to remove residual monomers, and dried to obtain a high-water content intraocular lens material 1-8.
[0104] Table 3: Composition of high water content intraocular lens materials
[0105]
[0106] HEMA: Hydroxyethyl Methacrylate
[0107] NVP: Vinylpyrrolidone
[0108] MPC: 2-methacryloyloxyethyl phosphorylcholine
[0109] EOEMA: Ethoxyethyl methacrylate
[0110] MMA: Methyl Methacrylate
[0111] EGDMA: ethylene glycol dimethacrylate
[0112] TMPTMA: trimethylolpropane trimethacrylate
[0113] ABVN: azobis(isoheptyl)nitrile
[0114] Example 3: Preparation of low water content intraocular lens material
[0115] As shown in Table 4, the following components were mixed separately until they were completely dissolved and stirred evenly. The resulting mixture was then transferred to a sealed, round, button-shaped mold with a diameter of 14 mm and a thickness of 3 mm for curing and molding. Curing was performed at 75°C for 6 hours and then at 100°C for 12 hours. After curing, polymer materials 9-17 were obtained.
[0116] The completely cured material was removed from the mold, and the material sheet was washed with acetone to remove residual monomers, and dried to obtain the bottom hydrated intraocular lens material 9-17.
[0117] Table 4: Low water content intraocular lens material composition
[0118]
[0119]
[0120] HEMA: Hydroxyethyl Methacrylate
[0121] HEA: Hydroxyethyl acrylate
[0122] POEA: Phenoxyethyl acrylate
[0123] PEA: Phenyl Ethyl Acrylate
[0124] PEMA: Phenyl ethyl methacrylate
[0125] EOEMA: Ethoxyethyl methacrylate
[0126] TFEMA: trifluoroethyl methacrylate
[0127] BA: Butyl acrylate
[0128] BDDA: Butanediol diacrylate
[0129] EGDMA: ethylene glycol dimethacrylate
[0130] AIBN: Azobisisobutyronitrile
[0131] BPO: Benzoyl peroxide
[0132] Example 4: Intraocular lens material performance test
[0133] 1. Test Method
[0134] 1.1 Transmittance test
[0135] The test method for the light transmittance of intraocular lenses and polymer materials refers to the test method taught by ISO 11979-2 or YY 0290.2. A spectrophotometer is used to measure and record the spectral transmittance (light transmittance) of the intraocular lens and polymer materials in the test solution (saline solution containing 0.9% NaCl) in the range of 300nm-1100nm with an aperture of 3mm.
[0136] 1.2 Glass transition temperature test method
[0137] The test method for the glass transition temperature of intraocular lenses and materials uses a differential scanning calorimeter to obtain the temperature-heat flow curve of the material at a heating rate of 10°C per minute and a temperature scanning range of -80-100°C to analyze the glass transition temperature of the material.
[0138] 1.3 Moisture content measurement method
[0139] The moisture content of intraocular lenses and materials is measured gravimetrically. The intraocular lens or material is fully hydrated to equilibrium in 35°C saline. After removal, quickly wipe off any surface moisture and weigh the hydrated sample. The sample is then dried in a vacuum oven at 60°C-80°C to a constant weight, and the dry mass is measured. The moisture content of the material at hydrated equilibrium = (hydrated mass - dry mass) / hydrated mass × 100%.
[0140] 1.4 Refractive index measurement method
[0141] The refractive index of intraocular lenses and materials is measured at 35°C. After temperature equilibrium, the refractive index value can be directly read using an Abbe refractometer. Prior to testing, the intraocular lens or material must be fully hydrated in 35°C saline to achieve equilibrium water content.
[0142] 1.5 “Flash” Measurement Method
[0143] The method for measuring the "flare" inside intraocular lenses and materials refers to the test method taught by the laboratory of Alcon Research Ltd. (Reference: Thomes BE, Callaghan TA. Evaluation of in vitro glistening formation in hydrophobic acrylic intraocular lenses. Clin Ophthalmol. 2013; 7:1529-1534. Doi:10.2147 / OPTH.S44208). The intraocular lens or material is placed in 45°C water for 24 hours. The sample is then transferred to 37°C water to equilibrate for 2.5 hours. The number and distribution of vacuoles (i.e., "flare") inside the intraocular lens or material sample are then observed under a microscope at 10× to 100× magnification.
[0144] 1.6 Implantation test during simulated surgery
[0145] The measurement method for the intraocular lens implantation test during simulated surgery refers to the test method taught by standards ISO 11979-3 or YY0290.3. Common surgical implantation instruments on the market, such as those from Alcon, Johnson & Johnson, Bausch & Lomb, or Medicel, are used. Implanters and viscoelastics suitable for surgical incisions of 1.8mm to 2.8mm are used. The operation is carried out according to the instructions of the instruments used. The intraocular lens maintains deformation for a period of 3 to 20 minutes. The intraocular lens is then injected into 35°C saline and the shape recovery of the intraocular lens is observed. After the intraocular lens is maintained in 35°C saline to simulate the intraocular state for 24 hours, the optical and mechanical properties are measured to see if there are any changes.
[0146] 2. Test results
[0147] After final drying, high-water-content intraocular lens materials 1-8 and low-water-content intraocular lens materials 9-17 were tested for moisture content, refractive index (RI@35°C), and glass transition temperature (Tg). After processing into intraocular lenses, intraocular lens materials 1-17 were tested for flare, implantation testing, illumination testing, and light transmittance. The test results are listed in Tables 5 and 6, respectively.
[0148] Table 5: Test results of high water content intraocular lens materials
[0149]
[0150] As shown in Table 5, by controlling the amount or ratio of the hydrophilic monomer in the polymer, the water content of the highly hydrated intraocular lens material can be controlled within a range of 15% to 65%, a relatively high water content, and no "flare" phenomenon was observed within the material. The resulting IOLs were tested for color change within a relatively short period of time, such as one to two months, after illumination testing. The saline solution used during the illumination test was collected and tested for cytotoxicity according to the test methods specified in ISO 10993-5 or GB / T 16886.5, and the results were non-toxic.
[0151] Table 6: Test results of low water content intraocular lens material performance
[0152]
[0153]
[0154] As shown in Table 6, by controlling the amount or ratio of hydrophilic monomers in the polymer, the water content of low-water-content intraocular lens materials can be controlled to between 1% and 3%. The amount of "flare" produced within the IOL is correlated with the material's water content. Materials with a water content below 1.5% exhibit more flare, while materials with a water content above 2% exhibit virtually no flare. Furthermore, due to the relatively low water content, the resulting IOLs require a longer time to change color during light exposure testing, typically between 2 and 6 months. The saline solution used during the light exposure test was collected and tested for cytotoxicity according to the test methods outlined in ISO 10993-5 or GB / T 16886.5, and the results were negative.
[0155] Example 5: Simulated intraocular light exposure test
[0156] The measurement method of the simulated intraocular illumination test refers to the test method taught by the standard ISO 11979-5 or YY 0290.5. The average length of time that the intraocular lens is exposed to sunlight after implantation can be considered to be 3 hours / day. The intraocular lens or material is placed in 35°C saline and moved to a position where it can be exposed to sunlight for 3 hours every day. The rest of the time, it is moved to a dark environment. The changes in the transmittance curve of the intraocular lens or material sample are tested every day until the transmittance curve stabilizes and no longer changes.
[0157] The light transmittance curves of the IOL made of high water content intraocular lens material 4 were tested before implantation and one month after simulated implantation. The test results are as follows: Figure 4 As shown. Figure 4As can be seen, the IOL of the present invention absorbs light with wavelengths of approximately 390nm to 520nm before implantation. One month after implantation, the IOL becomes colorless, and its transmittance gradually returns to normal levels. This change in absorbance helps patients undergoing intraocular lens surgery adapt to the transmitted light and achieves better postoperative visual acuity.
[0158] Figure 5 The IOL made of high water content intraocular lens material 4 before implantation ( Figure 5 Middle left) and 1 month after sham implantation ( Figure 5 Photo of the color change of the middle right. Figure 5 It can be clearly seen that the color of the IOL of the present invention changes from initial light yellow to colorless one month after simulated implantation.
[0159] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. Any technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.
Claims
1. A compound represented by formula (I-1) or (I-2): in, R1 is H, C 1-5 Alkyl; R2 is C 1-20 Alkylene; R3 is selected from H, -NH2, -OH, C 1-20 Alkyl, C 1-20 Alkoxy, -NHC 1-20 Oxygen, and -N(C 1-20 alkyl)2; and R c Does not exist or is C 1-5 alkyl; L is selected from -O-, -NH-, -CO-, -SO-, -SO2-, -N(C 1-20 alkyl)-, -CONH-, and -CON(C 1-20 alkyl)-; X is selected from O, S, CH2 and NH; and Q1, Q2 and Q3 are each independently selected from N, CH, and CR4, wherein R4 is selected from halogen, -OH, -NH2, -NO2, -CN, C 1-20 Alkyl, C 1-20 Alkoxy, -NHC 1-20 Alkyl, -N(C 1-20 Alkyl)2, -COOH, -COC 1-20 Alkyl, -COOC 1-20 Alkyl, -OC 1-20 Alkyl, -CONHC 1-20 Alkyl, -CON(C 1-20 alkyl)2, 6-20 membered aryl, and 5-20 membered heteroaryl.
2. The compound according to claim 1, wherein: R1 is H, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl or tert-butyl; and / or R2 is C 1-5 Alkylene; and / or R3 is selected from H, -NH2, -OH, C 1-5 Alkyl, C 1-5 Alkoxy, -NHC 1-5 Alkyl, and -N(C 1-5 alkyl)2; and / or R c is absent or is methyl; and / or L is selected from -O-, -NH-, -CO-, -SO-, -SO2-, -N(C 1-5 alkyl)-, -CONH-, and -CON(C 1-5 alkyl)-; and / or X is NH or CH2; and / or R4 is selected from halogen, -OH, -NH2, -NO2, -CN, C 1-5 Alkyl, C 1-5 Alkoxy, -NHC 1-5 Alkyl, -N(C 1-5 Alkyl)2, -COOH, -COC 1-5 Alkyl, -COOC 1-5 Alkyl, -OC 1-5 Alkyl, -CONHC 1-5 Alkyl, -CON(C 1-5 alkyl)2, phenyl, and 5-6 membered heteroaryl; and / or At most one of Q1, Q2 and Q3 is CR4, and the rest are CH.
3. The compound according to claim 1, wherein: R1 is H or methyl; and / or R2 is methylene or ethylene; and / or R3 is methyl or ethyl; and / or L is -O- or -NH-; and / or X is NH or CH2; and / or R4 is -NH2, -OH or -F; and / or In formula (I-1) A section has any of the following structures: and / or In formula (I-2) A section has any of the following structures:
4. The compound according to claim 1, wherein: R1 is H or methyl; and / or R2 is ethylene; and / or R3 is methyl; and / or L is -O- or -NH-; and / or X is NH; and / or R4 is -NH2 or -F; and / or In formula (I-1) A section has any of the following structures: and / or In formula (I-2) The section has the following structure:
5. The compound according to claim 1, wherein the compound is selected from the group consisting of:
6. A color-changeable polymer material comprising the compound according to any one of claims 1 to 5, wherein the amount of the compound is 0.01 wt% to 10 wt%, preferably 0.05 wt% to 5 wt%, and more preferably 0.1 wt% to 1 wt% of the color-changeable polymer material.
7. The color-changeable polymer material according to claim 6, wherein the water content is 15% to 65%; preferably 18% to 50%; or more preferably 22% to 45%; or the water content is 1% to 5%; preferably 1.5% to 3%; or more preferably 2% to 3%; and / or The refractive index of the color-changeable polymer material is greater than 1.42, preferably greater than 1.48, or more preferably greater than 1.
54.
8. Use of the compound according to any one of claims 1 to 5 or the color-changeable polymer material according to claim 6 or 7 in the preparation of an intraocular lens.
9. An intraocular lens comprising the compound according to any one of claims 1 to 5 or the color-changeable polymer material according to claim 6.